Geometric period Plithos burial ground at Chora of Naxos Island, Greece : anthropology report - Agelarakis, Anagnostis P., 1956- (Access archaeology., 2016)
This report aims offers glimpses of the human condition on Naxos Island, Greece, focussing on the archaeoanthropologic study of the human skeletal remains along with associated contexts of faunal materials recovered from the Geometric (9th -7th BC) component of the burial ground site of Plithos in Chora at Naxos island.